3D kinematics of the Sant Corneli anticline: insights from structural reconstruction and forward modelling - Mencos, J.; Muñoz, J. A.; Hardy, S. (TRABAJOS DE GEOLOGÍA, 2010)
The work presented here consists in the 3D structural reconstruction and forward modellingof a fault-related structure, the Sant Corneli anticline in the southern Pyrenees, from field and subsurfacedata. The process involves several steps: 3D digitalization, structural and stratigraphic analysis, surfaceconstruction, and numerical modelling. Each one of them can be adapted to the different natureof the surfaces under construction and to the origin of the data sets. 3D reconstruction is constrainedand/or completed by using a forward modelling technique for data extrapolation. Moreover, differentkinematic hypotheses can be tested. This three-dimensional approach permits a better understandingof areas with structural and stratigraphic complexities.